2014
DOI: 10.1051/0004-6361/201322406
|View full text |Cite
|
Sign up to set email alerts
|

AHerschel[C ii] Galactic plane survey

Abstract: Context. H i and CO large scale surveys of the Milky Way trace the diffuse atomic clouds and the dense shielded regions of molecular hydrogen clouds, respectively. However, until recently, we have not had spectrally resolved C + surveys in sufficient lines of sight to characterize the ionized and photon dominated components of the interstellar medium, in particular, the H 2 gas without CO, referred to as CO-dark H 2 , in a large sample of interstellar clouds.Aims. We use a sparse Galactic plane survey of the 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
184
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(202 citation statements)
references
References 55 publications
18
184
0
Order By: Relevance
“…This zone is well outside the cold and FUV-shielded core where most of the hydrogen is in H 2 and most of the carbon in CO (e.g., Roellig et al 2007). Recently, Herschel/HIFI observations demonstrated that a significant fraction, between 20% and 75%, of the ISM gas that is undetected in H Iand CO is bright in the [C II] FIR line at 158 μm (Langer et al 2014). Orr et al (2014) To summarize, the available data suggest that the Na I and K I absorption lines trace the warm (∼100 K) atomic envelope of the cold molecular CO gas in Taurus.…”
Section: Origin Of the Narrow Absorption In The Na I And K I Profilesmentioning
confidence: 99%
“…This zone is well outside the cold and FUV-shielded core where most of the hydrogen is in H 2 and most of the carbon in CO (e.g., Roellig et al 2007). Recently, Herschel/HIFI observations demonstrated that a significant fraction, between 20% and 75%, of the ISM gas that is undetected in H Iand CO is bright in the [C II] FIR line at 158 μm (Langer et al 2014). Orr et al (2014) To summarize, the available data suggest that the Na I and K I absorption lines trace the warm (∼100 K) atomic envelope of the cold molecular CO gas in Taurus.…”
Section: Origin Of the Narrow Absorption In The Na I And K I Profilesmentioning
confidence: 99%
“…In their derivation of the CO-dark H 2 gas fraction Langer et al (2014) used an exponential Galactic carbon abundance gradient N(C + )/N(H) ∝ exp(−R/6.2 kpc) following Wolfire et al (2003) and based on the [O/H] metallicity gradient at that epoch. This would imply a factor of two difference between the value at R = 8.5 kpc and that at the inner edge of the Galactic molecular ring at R = 4 kpc.…”
Section: Galactic Metallicity Gradientmentioning
confidence: 99%
“…Furthermore, the filling factor of the ionized gas appears larger relatively to the neutral gas. As a consequence of the low metallicity and low extinction in dwarf galaxies, it is possible that a significant fraction of the molecular gas is not traced by CO, but may be residing in the C + or C 0 -emitting region; for example (referred to as the "dark gas" in Wolfire et al 2010), this is quantified in low metallicity environments using C + by Poglitsch et al (1995) and Madden et al (1997) and, more recently, in our Galaxy by Langer et al (2014) and Pineda et al (2014).…”
Section: Introductionmentioning
confidence: 99%